Serum lipids in preterm infants fed a formula supplemented with nucleotides. - Tania Siahanidou; Mandyla, Helen; Papassotiriou, Ioannis; Anagnostakis, Dimitris (J Pediatr Gastroenterol Nutr, 2004)
BACKGROUND: The effect of dietary nucleotides on lipid metabolism has been the subject of clinical studies with conflicting results. We measured serum triglycerides, total cholesterol (total-C), and lipoprotein cholesterol levels (HDL-C, LDL-C, and VLDL-C) in preterm neonates fed formula with and without nucleotide supplements. METHODS: This prospective, randomized, controlled study included 150 healthy preterm neonates (gestational age, 33.0 +/- 1.9 weeks) matched for gestational age, birth weight, and gender. Subjects were assigned at birth to receive either a standard milk formula supplemented with nucleotides (group F-NT) or the same formula without nucleotides (group F). Serum was obtained before discharge (29.1 +/- 10.0 days of life) and triglycerides, total-C, and HDL-C were determined enzymatically. LDL-C and VLDL-C were estimated by the Friedewald formula. For statistical analysis t test, Mann Whitney-U test, two-way ANOVA, and chi2 test were used, as appropriate. The influence of several factors on serum lipid levels was evaluated by linear regression analysis. RESULTS: Serum triglycerides, total-C, and VLDL-C levels did not differ between groups. HDL-C levels (median; 25th-75th percentiles) were significantly higher (P < 0.001) in group F-NT (48.0 mg/dL; 40.5-57.0 mg/dL) than in group F (34.5 mg/dL; 27.2-44.0 mg/dL). On the contrary, LDL-C levels (median; 25th-75th percentiles) were significantly lower (P < 0.001) in group F-NT (39.0 mg/dL; 26.0-54.0 mg/dL) than in group F (65.0 mg/dL; 41.0-73.0 mg/dL). In the multiple regression analysis, nucleotide supplementation was identified as one of the controlled independent factors influencing serum HDL-C and LDL-C levels. CONCLUSIONS: Preterm neonates fed from birth with formula supplemented with nucleotides have significantly higher HDL-C and lower LDL-C serum levels than do neonates fed unsupplemented formula. The clinical relevance of these results remains to be elucidated.
Keywords: Analysis of Variance; Cholesterol; Female; HDL; Humans; Infant; Infant Formula; Infant Nutritional Physiological Phenomena; LDL; Lipid Metabolism; Lipids; Lipoproteins; Male; Newborn; Nucleotides; Premature; Prospective Studies; Regression Analysis; Triglycerides; VLDL